2017
DOI: 10.1016/j.ajog.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin for the prevention of preeclampsia and intrauterine growth restriction in women with a history: a randomized trial

Abstract: The use of enoxaparin in addition to standard high-risk care does not reduce the risk of recurrence of preeclampsia and small-for-gestational-age infants in a subsequent pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 48 publications
0
87
0
4
Order By: Relevance
“…These conditions are associated with preterm birth (PTB) and remain the leading cause of perinatal morbidity and mortality worldwide. Pathological mechanisms leading to preeclampsia and FGR display considerable overlap [134]. Infections, stress, substance abuse (e.g., smoking), maternal under-nutrition, chromosomal abnormalities, genetic and epigenetic modifications and syndromes with an unknown genetic (inherited) basis are primary mediators of FGR [135].…”
Section: Role Of Er Stress In Pregnancy Complications and Pretermmentioning
confidence: 99%
“…These conditions are associated with preterm birth (PTB) and remain the leading cause of perinatal morbidity and mortality worldwide. Pathological mechanisms leading to preeclampsia and FGR display considerable overlap [134]. Infections, stress, substance abuse (e.g., smoking), maternal under-nutrition, chromosomal abnormalities, genetic and epigenetic modifications and syndromes with an unknown genetic (inherited) basis are primary mediators of FGR [135].…”
Section: Role Of Er Stress In Pregnancy Complications and Pretermmentioning
confidence: 99%
“…Most recently, the large, well-designed HEPEPE and EPPI trials reported that enoxaparin with ASA does not significantly reduce placental-mediated complications, including preeclampsia, when compared to aspirin alone [31,32]. The conclusions of systematic reviews and meta-analyses summarizing this literature are conflicting.…”
Section: Lmwh For Preeclampsia Prevention: Evidence From Clinical Trialsmentioning
confidence: 85%
“…The criteria utilized to identify women as 'high risk' of developing preeclampsia have thus far differed greatly between trials. The majority of trials utilized inclusion criteria of prior preeclampsia, placental-mediated complication or pregnancy loss to identify women who are considered at high risk of preeclampsia in the current pregnancy; this was the approach in the recent HEPEPE and EPPI trials [31,32]. The primary outcome of these clinical trials has typically consisted of a composite clinical outcome, including preeclampsia, small for gestational age, placental abruption, and maternal or perinatal death.…”
Section: Patient Selectionmentioning
confidence: 99%
“…However, LMWH does not appear to significantly reduce the rates of pre‐eclampsia or SGA births when used alone, suggesting that is has synergetic effects with aspirin. Despite these promising findings, several recent large multicenter trials, such as the EPPI , HEPEPE and TIPPS trials, did not find similar beneficial effects of LMWH therapy for pre‐eclampsia prevention. Furthermore, the use of heparin and its derivatives for the prevention of pre‐eclampsia carries more potential risk than the use of low‐dose aspirin, such as bleeding and heparin‐induced thrombocytopenia, although such risks were demonstrated to be minimal in recent randomized clinical trials .…”
Section: Current Pharmacological Interventionsmentioning
confidence: 96%
“…Despite these promising findings, several recent large multicenter trials, such as the EPPI , HEPEPE and TIPPS trials, did not find similar beneficial effects of LMWH therapy for pre‐eclampsia prevention. Furthermore, the use of heparin and its derivatives for the prevention of pre‐eclampsia carries more potential risk than the use of low‐dose aspirin, such as bleeding and heparin‐induced thrombocytopenia, although such risks were demonstrated to be minimal in recent randomized clinical trials . One of the primary limitations of these large trials is the inclusion of all patients with the pre‐eclamptic syndrome without consideration of the underlying etiology, thereby diluting the potential efficacy of LMWH therapy, which may benefit only a subset of patients.…”
Section: Current Pharmacological Interventionsmentioning
confidence: 96%